2008
DOI: 10.2139/ssrn.1282611
|View full text |Cite
|
Sign up to set email alerts
|

Lending Interest Rate Pass-Through in the Euro Area: A Data-Driven Tale

Abstract: The harmonized MIR retail interest rates for the euro area, available as of January 2003, show remarkable differences both in levels and dynamics with the previous unharmonized NRIR rates.This evidence should suggest caution in extrapolating the findings of the NRIR-based literature on the incomplete long-run pass-through of market rates even into the short term business lending rates, the least sticky ones among bank rates. We show that long run pass-throughs for MIR rates of smaller and larger short-term bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Depuis Cottarelli et Kourelis (1994), de nombreuses études ont quantifié cette transmission des taux directeurs aux taux bancaires. Leurs conclusions sont assez sensibles au modèle précisément testé (Sander et Kleimeier, 2004) ainsi qu'aux échantillons retenus (Marotta, 2008). Une conclusion commune à l'ensemble de ces travaux est que malgré le processus d'intégration économique et de libéralisation, d'importantes hétérogénéités sont perceptibles selon les marchés analysés.…”
Section: Le Canal De Transmission Des Prix Immobiliers Dans Les Pays De La Zone Eurounclassified
“…Depuis Cottarelli et Kourelis (1994), de nombreuses études ont quantifié cette transmission des taux directeurs aux taux bancaires. Leurs conclusions sont assez sensibles au modèle précisément testé (Sander et Kleimeier, 2004) ainsi qu'aux échantillons retenus (Marotta, 2008). Une conclusion commune à l'ensemble de ces travaux est que malgré le processus d'intégration économique et de libéralisation, d'importantes hétérogénéités sont perceptibles selon les marchés analysés.…”
Section: Le Canal De Transmission Des Prix Immobiliers Dans Les Pays De La Zone Eurounclassified
“…While other studies have found a complete passthrough especially in the long term, among others, Qayyum, et al (2005), Durán-Víquez and Esquivel-Monge (2008), and Ozdemir (2009). But Marotta (2008) finds a near-complete pass-through in the EMU and Greek. Associated with asymmetric responses to changes in policy rates, Durán-Víquez and Esquivel-Monge (2008) found no asymmetry occurring for cases in Costa Rica.…”
Section: Introductionmentioning
confidence: 99%
“…Many IRPT-related studies have been conducted such as Bredin et al (2001), Espinosa-Vega and Rebucci (2003), Tieman (2004), Qayyum, et al (2005), Durán-Víquez and Esquivel-Monge (2008), Maskay and Pandit (2009), Ozdemir (2009), Egert, et al (2007), Kwapil and Scharler (2006), Sorensen and Werner (2006), Marotta (2008), Rehman (2009), Samba and Yan (2010), Kot (2004) and Kobayashi (2008). There are two main approaches used in previous studies to calculate the degree of IRPT.…”
Section: Introductionmentioning
confidence: 99%